Foraminifera Iodine to Calcium Ratios: Approach and Cleaning - Winkelbauer, Helge (2021)
Planktic and benthic foraminiferal iodine (I) to calcium (Ca) molar ratios have been proposed as an exciting new proxy to assess subsurface and bottom water oxygenation in the past. Compared to trace metals, the analysis of iodine in foraminiferal calcite is more challenging, as iodine is volatile in acid solution. Here, we compare previous analyses that use tertiary amine with alternative analyses using tetramethylammonium hydroxide (TMAH) and ammonium hydroxide (NH4OH) to stabilize iodine in solution. In addition, we assess the effect of sample size and cleaning on planktic and benthic foraminiferal I/Ca. Our stabilization experiments with TMAH and NH4OH show similar trends as those using tertiary amine, giving relatively low I/Ca ratios for planktic and benthic foraminifera samples from poorly oxygenated waters, and high ratios for well-oxygenated waters. This suggests that both alternative methods are suitable to stabilize iodine initially dissolved in acid. Samples that contain 5–10 specimens show a wide spread in I/Ca. Samples containing 20 specimens or more show more centered I/Ca values, indicating that a larger sample size is more representative of the average planktic foraminifera community. The impact of cleaning on planktic and benthic foraminifera I/Ca ratios is very similar to Mg/Ca, with the largest effect occurring during the clay removal step. The largest iodine contaminations were recorded at locations characterized by moderate to high organic carbon contents. In those circumstances, we recommend doubling the oxidative cleaning steps (4 instead of 2 repetitions) to ensure that all organic material is removed.